Rethinking the Kurdish movement: the role of the neighborhood assemblies in Diyarbala.r - Tuncel, Deniz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
Based on the judicial violence of the Turkish state against the Kurds after 2009 and the attempts of the Kurdish political movement for the implementation of participatory politics at a local level since 2005, this thesis argues how the Kurds have been pushed out of legal order and rendered silenced by the Turkish judiciary, and how the Kurdish movement used the neighborhood assemblies to enable the Kurds to have the representation of their own voice. The case studies of the thesis are accordingly composed of the KCK trial and the neighborhood assemblies in Diyarbak1r. By exploring the process of the KCK trial, it argues that the Turkish judiciary as an institution of the sovereign power, through Schmitt, Agamben, Jakobs and Benjamin, decides the state of exception and makes "friend-enemy distinction" among its citizens concerning the security of the political and judicial order of the state. By observing the process of the decision-making processes from neighborhood to municipal level and, it asserts that the Democratic Autonomy is a practice of freedom of the Kurds and other subaltern communities, who were pushed out of legal order and mobilized outside the borders of that legal order, and the local assemblies founded by the Kurdish movement as the instruments of bottom-up democracy emerged as a space of struggle that were constituted by and constitutive of a community of struggle.
Keywords: Kurds -- Government policy -- Turkey.; Kurds -- Turkey -- Government relations.; Kurds -- Turkey -- Politics and government -- 21st century